ANALISIS PENGARUH KUAT ARUS LISTRIK TERHADAP KETEBALAN PELAPISAN PERAK PADA ALUMUNIUM A6063 DENGAN PROSES ELECTROPLATING - Kisworo Sabekti; Gery Setiadi Mansjur; Jenny Primanita Diningrum (Jurnal Ilmiah Teknik Mesin, 2018)
Electroplating is the process of coating metal surfaces with electrochemical methods. The use ofaluminum material as a conductor in gas insulated switchgear is no other because aluminummaterial is lighter and cheaper than other metals. But in terms of delivering aluminum electriccurrent it is more difficult because it has a greater type of resistance than copper and silver.Therefore, the conductor connection made from aluminum will be coated with copper and silverto facilitate the supply of electric current. The coating process uses electroplating method. Theelectroplating for coating process uses current strengths 0.2 A, 0.3 A, and 0.4 A. From variousvariations of the current strength will affect the thickness of the coating. The results of this studyindicate that the higher the current strength is directly proportional to the thickness of the layer.The thickness of the electroplating process that uses current strengths 0.2 A, 0.3 A, and 0.4 Arespectively is 10.88 μm, 18.83 μm, and 28.18 μm. Whereas in testing conduct electricity to theworkpiece with a silver thickness of 10.88 μm less than the workpiece with a silver thickness of18.83 μm and 28.18 μm.